Pelatihan Pembuatan Lilin Aromaterapi Dari Minyak Jelantah Untuk Guru SMP di Kabupaten Bintuni - Jan Hendriek Nunaki; Mujasam Mujasam; Nur Indah Ririn Fitriani Nasir; Budi Santoso; Rintar A. Simatupang; Insar Damopolii (JURNAL ABDIMAS DOSMA (JAD), 2025)
Used cooking oil is a liquid material produced from the use of oil for frying. This oil is often not reused and is simply thrown into the environment. If you throw it in the sink it will cause a blockage. Throwing it out in the open causes pollution. The dedication aims to train junior high school teachers in managing used cooking oil into aromatherapy candles in various colors. 25 teachers were involved in the competition. They are spread across two schools in Bintuni district, West Papua. Data was collected using a questionnaire. The results of the service show that they are 100% interested in the activities they have carried out. Most of their knowledge (86.96%) is very good in managing used cooking oil into products with useful value. The other percentage shows good understanding. The results of the service indicate that junior high school teachers have succeeded in absorbing information and improving their skills in producing aromatherapy candle products from used oil.